Sams teach yourself FreeBSD in 24 hours - Urban, Michael C. (Sams Pub., 2003)
Annotation
Includes index. - Print version record
Keywords: FreeBSD; Free computer software; Operating systems (Computers); Logiciels gratuits; Systèmes d'exploitation (Ordinateurs); operating systems; COMPUTERS; Operating Systems; General